Comments on “Economic Ordering Frequency for Two Items Jointly Replenished” by Frank T. Shu - Kalro, Amarlal H. (Management Science, 1972)
In his paper (Management Science, Vol. 17, No. 6, pp. B-406–B-410) Shu describes a method for determining the replenishment frequencies of items jointly replenished. Essentially, the procedure develops “skipping rules” for an item, this being replenished every kth time that the others are replenished. A better procedure is to rank the items in decreasing order of demand/set-up cost ratio, then select the lowest ratio item as the skipped item.